Linearizing control based on adaptive observer for anaerobic continuous sulphate reducing bioreactors with unknown kinetics - Neria-Gonzalez, M. I. (Array, 2009)
Summary: Anaerobic reactors are a typical example of processes that exhibit non-linear behavior and, also time varying parameters; hence their operation is known to be difficult to model and control. In contrast to modeling approaches, in practice linear controllers are widely employed for industrial processes because of their easy implementation and manipulation by plant operators; nevertheless linear approaches are not robust when the operating conditions change suddenly and/or strong disturbances are present. In order to introduce robust controllers to these processes, this paper addresses the tracking problem for the substrate (sulphate) control in a class of continuous bioreactors. An experimentally corroborated bioreactor model serves as benchmark problem for advanced non-linear analysis and control techniques; taking into account system non-linearities, stability and performance objectives over large operating regions. It is considered that, as it is common in practice, the rate of substrate consumption exhibits uncertainty. Results show that the proposed controller exhibits better dynamic performance than a classical Proportional-Integral control tuned using the methodology suggested by Internal Model Control